PUBLIC DIPLOMACY AS AN INSTRUMENT FOREIGN POLICY - Daimah Daimah (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The development of the world situation, actors, and information technology make the direction of diplomacy traditional diplomacy shifts to more modern diplomacy, in this case public diplomacy. The development of information technology makes the choices of diplomacy tools become diverse. Previously, diplomacy was colored by related issues with 'war', now that's the issue increasingly shifting. War is not non-existent, but emergence of other issues such as the environment, tourism, terrorism, health, human rights are the targets of public diplomacy. The purpose of this research is to know the role of public diplomacy as an instrument of foreign policy and conclude the role of public diplomacy as a strategy for achieving foreign policy . The research specification used in this research is descriptive type of analysis and literature review which focuses on searching for both primary and secondary data. Public diplomacy is interpreted as a process of government communication to the public foreign countries which aims to provide an understanding of the country, attitudes, institutions, culture, national interests, and the policies taken by the country . Impact caused include the political, economic, social, and in its implementation no longer monopolized by the government . This study focuses on the problems of why public diplomacy is used as an instrument of foreign policy (conceptual ), how is the communication strategy in public diplomacy to determine foreign policy and how Soft Power influences the framework of public diplomacy in foreign policy. The results of the study indicate that public diplomacy has a major influence on the decision to determine foreign policy.